Baseline states of organic constituents in the Athabasca river system upstream of Fort McMurray ... - Peake, E.; Strosher, M. T. (University of Alberta Library, 1979)
Investigations were carried out on the Athabasca River upstream of Fort McMurray to determine the baseline quantities of organic constituents and their contribution to the organic water quality of the river system as it continues through the Athabasca Oil Sands strip mining area. Results of these investigations were evaluated to assess the fate of organic matter in this segment of the river. Studies focussed on the natural occurrence of classes of compounds which are known to be major constituents of wastewaters from oil sands processing. Major groups of naturally occurring organic compounds and a limited number of labile compounds were also considered as a means of assessing the assimilative capacities of this river segment. Water soluble constituents, tannins and lignins, asphaltenes, and polar constituents were the major organic components of the river system as determined from the 16 different investigations carried out. Water samples contained an average 9 mg/l of organic carbon, the majority of which ...